KODE AKSI NASKAH DRAMA SANG MANDOR KARYA RAHMAN ARGE (TINJAUAN SEMIOTIKA ROLAND BARTHES) - Dirmawati; Andi Saadillah (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
In human life, literature has a very vital function. One of these functions is as a place to manifest all human feelings and thoughts. Imagine, literature is a classification of an abstraction. That is, literature is used as a medium in describing things that are abstract in life into something that makes sense. One type of literary work that describes this is drama. In contrast to other literary works, drama has certain advantages that include three dimensions, namely the dimensions of literature, movement, and speech. The script for the drama Sang Foreman by Rahman Arge is a very interesting story to study, which contains many elements of South Sulawesi culture, especially the Bugis-Makassar people. The foreman's drama script is full of codes and signs. In particular, this study examines the code of action from Roland Barthes' semiotic review. Keywords: Code, Action, Semiotics, Drama